The Value of Prognostic Nutritional Index (PNI) in Predicting Survival and Guiding Radiotherapy of Patients With T1-2N1 Breast Cancer - Hua, Xin; Long, Zhi-Qing; Huang, Xin; Deng, Jia-Peng; He, Zhen-Yu; Guo, Ling; Zhang, Wen-Wen; Lin, Huan-Xin (Frontiers in Oncology, 2020)
Background: To investigate the significance of the prognostic nutrition index (PNI) as a predictor of survival and guide for treating T1-2N1 breast cancer. Methods: Patients with T1-2N1 breast cancer (N = 380) who underwent a mastectomy at our Center were studied. PNI was calculated as 10 × serum albumin (g/dL) + 0.005 × total lymphocyte count (per mm3). The cut-off for the PNI was calculated using the time-dependent receiver operating characteristic (ROC) curve analysis by overall survival (OS) prediction. The associations between the PNI and the clinicopathologic characteristics were analyzed using Pearson’s χ2 test. Survival curves were calculated using the Kaplan-Meier method. Univariate and multivariate analyses were performed using the Cox proportional hazards model. Results: Subgroup analyses of patients with low PNI value (≤52.0) and high PNI value (>52.0) showed that a high PNI was significantly associated with HER2 status, the neutrophil-lymphocyte ratio (NLR), the monocyte-lymphocyte ratio (MLR) and KI 67 status. The OS of patients with a high PNI was significantly better than that of patients with a low PNI. We then conducted subgroup analyses based on PNI and radiotherapy. Among patients who received radiotherapy, the OS of those with a high PNI was significantly better than that of patients with a low PNI. Among patients with a high PNI, the OS of those who received radiotherapy was better than that of the patients who did not receive radiotherapy. However, among the patient with a low PNI, the OS of those who received radiation was worse than that of patients who did not receive radiotherapy. The Kaplan-Meier survival analysis and the multivariate analysis of patients with T1-2N1 breast cancer who received radiotherapy showed PNI independently predicted OS. Conclusions: The preoperative PNI may be a reliable predictor of OS of patients with operable T1-2N1 breast cancer, with the capacity to provide a personalized prognosis and facilitate the development of clinical treatment strategies. However, radiotherapy did not achieve satisfactory outcomes in patients with PNI ≤52.0; thus, further studies on treatment optimization are needed.